PRR11 promotes cell proliferation by regulating PTTG1 through interacting with E2F1 transcription factor in pan-cancer - Zhang, Haibo; He, Ziqing; Qiu, Li; Wei, Jinfen; Gong, Xiaocheng; Xian, Mingjian; Chen, Zixi; Cui, Ying; Fu, Shuying; Zhang, Zihao; Hu, Bowen; Zhang, Xiquan; et al. (Frontiers in Molecular Biosciences, 2022)
The overexpressed proline rich (PRR11) plays a critical role in cancer progression. The relevant biological functions of PRR11 in pan-cancer development are not well understood. In the current study, we found that PRR11 was up-regulated in 19 cancer types compared with that of normal tissues and high-expressed PRR11 was a predictor of poor prognosis in 10 cancer types by bioinformatics. Then, we showed that interfering PRR11 on three cancer cell lines could greatly inhibit cell proliferation and migration, and arrest cells to S phase in vivo. Based on RNA-seq, downregulation of E2F1 expression could extremely suppress the expression of PTTG1 and cell cycle pathway by differential gene analysis and enrichment analysis. The expression of PRR11 and PTTG1 was positively correlated in TCGA and independent GEO datasets. Importantly, we found the PRR11 expresses in nuclear and could interact with E2F1 on PTTG1 promoter region to increase the expression of PTTG1. Further results indicated that the expression of PTTG1 was also associated with poor prognosis in 10 cancer types and downregulation of PTTG1 expression could inhibit cancer cell proliferation and migration. Therefore, we found that PRR11 served as an oncogene in pan-cancer, and PRR11 could influence the cell cycle progression through regulating the expression of PTTG1 by interacting with transcription factor E2F1.